Beyond Computer Aided Design: Holographic Collaboration in Enhancing Product Life Management - Pesculis, James; Pavlovich, Robert J.; Montalvo-Ruiz, Eisen; Sullivan, Christopher P. (Proceedings. Annual Reliability and Maintainability Symposium, 2025)
For aerospace and defense companies, the US government's initiative to implement comprehensive digital thread frameworks becomes imperative to improving reliability and maintainability (R&M) performance across complex product lifecycle management (PLM) processes and global supply chains. Targeted digital transformation efforts, that challenge standard processes through research and development of innovative technologies and novel approaches, can provide incremental contributions to business process improvement that unlock customer value by enabling personnel to work differently through new digital capabilities. Developing manufacturing capabilities that incorporate R&M principles, particularly in the aerospace and defense industry, is key to lowering production costs and speeding time to market by gaining manufacturing efficiencies and reducing risks on multi-million or billion-dollar programs prior to entering production. To realize these efficiencies and reduce risk, advanced visualization capabilities offer new approaches to system design and development to create significant improvement opportunities targeted at select PLM use cases. Through immersive interactive experiences created with the assistance of digital design tools, techniques, and ideation spaces, engineers can generate novel approaches to improve the product design process through the insertion of digital technology. These opportunities reach beyond the decades old 2D and 3D computer aided design (CAD) technology to include the realm of extended reality (XR). One such approach includes the use of XR hardware and software to allow one or more persons to collaborate on full-scale holographic models in real-world space, whether in the same physical space or joined remotely. With the release of enterprise-level head mounted spatial computers (HMSCs) in the commercial market, holographic collaboration use cases now have practical industrial applications in areas including digital prototyping, design reviews, human factors analysis, work instruction validation, factory layouts, mission operations analysis, and customer product reviews. This realization has led our team to add a holographic collaboration project to our roadmap with research objectives to assess the practical application of collaborative holographic technology and its potential return on investment (ROI). This paper highlights the approach, methodology, and results of that endeavor.